The Impact of COVID-19 Pandemic on the Diagnosis, Treatment, and Outcomes of Colorectal Cancer in Singapore - Hui Lionel Raphael Chen; Piea Peng Lee; Yun Zhao; Wei Hao Caleb Ng; Jiashen Zhao; Yu En Christopher Tan; Bo Jie Sean Loh; Kah-Hoe Pierce Chow; Hiang Khoon Tan; Kwong-Wei Emile Tan (Medicina)
Background and Objectives: During the COVID-19 pandemic, many countries implemented lockdowns and social distancing measures, which may delay the early diagnosis of colorectal cancer (CRC). This study aims to review the impact of the pandemic on the diagnosis and treatment outcomes of CRC. Materials and Methods: Patients who underwent colonoscopy or surgery for CRC were included. The study was divided into the pre-COVID-19 (January 2019–January 2020), early COVID-19 (February–May 2020), recovery (June–December 2020), and heightened alert (January–December 2021) periods. Cox regression was used to model the waiting time to colonoscopy. Multivariable logistic regression identified associations between time periods and incidence of CRC diagnosed. The characteristics and outcomes of the surgical procedures that were performed were compared across the time periods. Results: A total of 18,662 colonoscopies and 1462 surgical procedures were performed in the study period. Compared to the pre-COVID-19 period, there was a longer time to colonoscopy during the recovery (HR: 0.91; 95% CI: 0.87, 0.94) and heightened alert periods (HR: 0.88; 95% CI 0.85, 0.91). The early COVID-19 (OR: 1.36; 95% CI: 1.04, 1.77) and recovery (OR: 1.20; 95% CI: 1.01, 1.43) periods were associated with higher odds of diagnosing CRC. Compared to the pre-COVID-19 period, there was a higher proportion of ASA 4 patients (4.3% vs. 1.3%; p < 0.001) and stage 4 CRC patients (22.2% vs. 16.9%; p = 0.001) that required surgery during the heightened alert period. Similarly, there was a higher proportion of emergency surgeries (22% vs. 13.3%; p = 0.002); diverting stomas (13.5% vs. 10.5%; p = 0.005), and Hartmann’s procedures (4.4% vs. 0.4%; p = 0.001) performed during the heightened alert period. Conclusions: The pandemic was associated with a higher proportion of metastatic CRC patients requiring surgery. Healthcare policies should facilitate early cancer screening, diagnosis, and treatment to reduce cancer-related morbidity for future pandemics.